The differences between glazing with solutions, coating with fish waste extracted gelatin and polyethylene-packaging of common carp fish fil-lets and their effects on qualitative and sensory characteristics during different freezing storage periods - Hussein, Ahmed A.; Ahmed, Mahmoud M. (Journal of Kerbala for Agricultural Sciences, 2022)
The study was conducted to choose the best way to store the fillets of common carp fish. Samples were divided into five treatments (T1 control treatment), (T2 glazing with saline solution 2%), (T3 glazing with acid solution 2%), (T4 coating with fish ex-tracted Gelatin), (T5 normal polyethylene- packaging). These five groups (treat-ments) have been stored in freezing conditions at four periods 2,4,6,8 weeks respectively. The qualitative and sensory properties of fish fillets were studied and the best results was belonging to T4 (gelatin coating treatment). The study included the process of gelatin extraction from fish waste as well.